PENGARUH PEMBERIAN SARI DAUN CINCAU HIJAU (PREMNA OBLONGIFOLIA MERR) TERHADAP KADAR KOLESTEROL HDL DAN KOLESTEROL LDL TIKUS SPRAGUE DAWLEY DISLIPIDEMIA - Astirani, Ananda Eka; Rahayuningsih, Hesti Murwani (Journal of Nutrition College, 2012)
Background : Dyslipidemia is an increase in total cholesterol, LDL-cholesterol and triglycerides and also decrease HDL-cholesterol concentration from normal range. Restricting fat consumption, increasing intake of fruits and vegetables rich in fiber and antioxidant can help manage dyslipidemia. Green grass jelly (Premna oblongifolia Merr) rich in fiber and chlorophyll which can increase HDL-cholesterol and decrease LDL cholesterol. Objective : to analyze the effect of green grass jelly extract on HDL-cholesterol and LDL-cholesterol alteration. Methods : This research was experimental laboratory using pre-post test with randomized control groups design. Sample were male Sprague Dawley rats, 7-8 weeks old, inducted dyslipidemia, given green grass jelly diet using 2,7 ml and 5,4 ml dosage for 28 days. HDL-cholesterol and LDL-cholesterol were measured by CHOD-PAP and diasis reagent. Normality data were tested by Saphiro Wilk test. Data were analyzed by paired t test/wilcoxon and Anova/ Kruskal wallis. Result : Green grass jelly (Premna oblongifolia Merr) extract 5,4 ml/day can significantly increase HDL-cholesterol in Sprague dawley dyslipidemia rats from 22,29Â±4,82 mg/dl to 27,29Â±3,82 mg/dl (p<0,05) but have no effect for decreasing LDL-cholesterol serum. Conclusion : Green grass jelly (Premna oblongifolia Merr) extract 5,4 ml/day can significantly increase HDL-cholesterol in Sprague dawley dyslipidemia rats for about 22%.